Pentingnya mempunyai waktu tidur yang cukup terutama untuk kalangan para remaja - rahmaniyah, furoidah nur (Maliki Interdisciplinary Journal, 2026)
Adequate sleep is a basic need that can maintain physical and mental health. However, many teenagers tend to neglect the duration and quality of sleep due to study activities, gadget use, and changes in lifestyle. This study aims to illustrate the importance of adequate sleep. Several methods were used, including descriptive research, observation, and brief interviews with a group of teenagers aged 15-18 years. The results indicate that most teenagers who do not get enough sleep (more than 7 hours per night) experience several symptoms such as decreased concentration, fatigue, mood swings, and decreased academic performance and grades. Furthermore, sleep deprivation also increases the risk of stress and minor health problems such as headaches and a decreased immune system. Conversely, when teenagers get sufficient and good sleep, they will show more stable physical conditions, more controlled emotions, and optimal learning abilities. This opinion confirms that adequate sleep is a crucial factor that needs to be considered in efforts to maintain health and balance adolescent activities.